Scoop [videorecording (DVD)] - Allen, Woody, 1935-; Allen, Woody, 1935-; Allen, Woody, 1935-; Jackman, Hugh; Johansson, Scarlett, 1984-; McShane, Ian, 1942-; Dance, Charles; Garai, Romola, 1982- (Universal Pictures, 2006)
Sondra Pransky is a lowly college newspaper reporter in London for the summer visiting friends. Brought onstage by magician Sid Waterman one night during his act, Sondra is visited by the spirit of famous journalist Joe Strombel while inside one of Sid's "magic" boxes. Given the scoop of a lifetime on the possible identity of the famous tarot card serial killer by the apparition, Sondra, with Sid in tow, tries to infiltrate the aristocratic life of Peter Lyman, only to find a romantic entanglement with the gentleman puts a damper on her efforts to gather the evidence and write a career-making scoop.